Strategi keberlanjutan pengelolaan hutan larangan adat Kenegerian Rumbio Kabupaten Kampar Propinsi Riau - Budi Azwar; Defri Yoza; Husni Thamrin; Elfiandri Elfiandri (Dinamika Lingkungan Indonesia, 2021)
This study was carried out in the Kenegerian Rumbio customary forest area in Kampar Regency, Riau Province. The purpose of this study was to analyze priority strategic alternatives in sustainable management of Kenegerian Rumbio customary forest prohibitions in Kampar Regency. This research is descriptive research with quantitative research design. With the help of experts, FGD (focus group discussion) is carried out to obtain a priority hierarchy structure. Analysis method using AHP (analysis hierarchy process) technique. The research was conducted in the Area of Rumbio Kenegerian Customary Prohibition Forest Kampar Regency, Riau Province, starting from March to December 2019. The results of the study was identified that the alternative main priority strategy in the management of customary prohibited forests is the empowerment of forest area communities, following the subsequent strategy of strengthening traditional institutions. Furthermore alternative strategies for optimizing economic benefits and expanding cooperation networks. In the implementation of community empowerment strategies in forest areas, synergy between stakeholders in policies, programs, operational steps, goals, targets and targets of periodicity needs to be built.